The paradigm of the prince: the leader, the reason of State and the electronic means - Protzel, Javier (1994)
In this text it was suggested that the different forms of relationship between governments and television channels, since the seventies, have responded in one way or another but, according to some models that I present here, to propaganda imperatives and, in many cases, of control. Moreover, these tasks have often been conceived and executed not from the civil administration, but underground from military concepts such as the "psychological warfare".